Association between Genetic Variants and Diabetes Mellitus in Iranian Populations: A Systematic Review of Observational Studies - Mehrnoosh Khodaeian; Samaneh Enayati; Ozra Tabatabaei-Malazy; Mahsa M. Amoli (Journal of Diabetes Research)
Introduction. Diabetes mellitus as the most prevalent metabolic disease is a multifactorial disease which is influenced by environmental and genetic factors. In this systematic review, we assessed the association between genetic variants and diabetes/its complications in studies with Iranian populations. Methods. Google Scholar, PubMed, Scopus, and Persian web databases were systematically searched up to January 2014. The search terms were “gene,” “polymorphism,” “diabetes,” and “diabetic complications”; nephropathy, retinopathy, neuropathy, foot ulcer, and CAD (coronary artery diseases); and Persian equivalents. Animal studies, letters to editor, and in vitro studies were excluded. Results. Out of overall 3029 eligible articles, 88 articles were included. We found significant association between CTLA-4, IL-18, VDR, TAP2, IL-12, and CD4 genes and T1DM, HNFα and MODY, haptoglobin, paraoxonase, leptin, TCF7L2, calreticulin, ERα, PPAR-γ2, CXCL5, calpain-10, IRS-1 and 2, GSTM1, KCNJ11, eNOS, VDR, INSR, ACE, apoA-I, apo E, adiponectin, PTPN1, CETP, AT1R, resistin, MMP-3, BChE K, AT2R, SUMO4, IL-10, VEGF, MTHFR, and GSTM1 with T2DM or its complications. Discussion. We found some controversial results due to heterogeneity in ethnicity and genetic background. We thought genome wide association studies on large number of samples will be helpful in identifying diabetes susceptible genes as an alternative to studying individual candidate genes in Iranian populations.